2017
DOI: 10.3389/fimmu.2017.01528
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Propofol vs. Isoflurane Anesthesia on Postoperative Changes in Cerebrospinal Fluid Cytokine Levels: Results from a Randomized Trial

Abstract: IntroductionAside from direct effects on neurotransmission, inhaled and intravenous anesthetics have immunomodulatory properties. In vitro and mouse model studies suggest that propofol inhibits, while isoflurane increases, neuroinflammation. If these findings translate to humans, they could be clinically important since neuroinflammation has detrimental effects on neurocognitive function in numerous disease states.Materials and methodsTo examine whether propofol and isoflurane differentially modulate neuroinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 37 publications
(58 reference statements)
2
26
0
1
Order By: Relevance
“…We also encourage future research on the mechanism of the functional connectivity changes after surgery. A review of effects of general anesthesia on the brain [99] raises some mechanistic possibilities, including impaired neurotrophin signaling and inflammation [100]. …”
Section: Discussionmentioning
confidence: 99%
“…We also encourage future research on the mechanism of the functional connectivity changes after surgery. A review of effects of general anesthesia on the brain [99] raises some mechanistic possibilities, including impaired neurotrophin signaling and inflammation [100]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown higher proinflammatory cytokine levels in serum and cerebrospinal fluid (CSF) of patients with postoperative delirium, POCD, and/or AD . CSF MCP‐1 levels and monocyte numbers increase from 1 hour before to 24 hours after surgery/anesthesia . In a pilot study, we found that CSF monocyte MCP‐1 receptor expression decreased 24 hours after surgery in patients who later developed POCD, suggesting that increased monocyte chemoattractant protein 1 (MCP‐1) levels induce monocyte influx into the central nervous system and monocyte MCP‐1 receptor downregulation…”
mentioning
confidence: 77%
“…The monocyte‐to‐lymphocyte ratio is used to evaluate these two major leukocyte populations in CSF as recently described . CSF supernatant is analyzed using multiplex enzyme‐linked immunosorbent assay (ELISA) to measure levels of the cytokines MCP‐1, interleukin (IL)‐6, IL‐8, and granulocyte colony‐stimulating factor (G‐CSF) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations